Temperature reduction pinch analysis (TERPA) : application of pinch analysis for tree planting targeting - Sivanyanam Ravinttiran, 1993-, author; Ho, Wai Shin, 1986-, supervisor; Fakulti Kejuruteraan Kimia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Sains (Pengurusan Tenaga)) - Universiti Teknologi Malaysia, 2017